THE EFFECT OF THE SPIRIT OF NATIONALISM AND CINTA TANAH AIR ON THE SELF INDEPENDENCE OF ELEMENTARY SCHOOL STUDENTS - Deva Indah Saputri; Herwin Herwin (JMIE (Journal of Madrasah Ibtidaiyah Education), 2020)
The research aims to determine the effect of the attitude of the spirit of nationalism and cinta tanah air on the independence of elementary school students. This study uses a quantitative approach with ex-post facto methods. The population in this study were high class students, namely class IV, V, and VI of state elementary schools in Masaran Subdistrict, Sragen. The research sample of 100 students randomly selected. Data collection techniques use a psychological scale. Data collection instruments use a scale of independence. Data analysis techniques used are partial correlation and multiple regression. Analysis prerequisite test uses normality, linearity and multicollinearity test. The results showed that the spirit of nationalism partially significantly affected the independence of students, the cinta tanah air partially significantly affected the independence of students, the spirit of nationalism and cinta tanah air simultaneously significantly affected the independence of students.